Un-‘Egg’-Plored: Characterisation of Embryonation in the Whipworm Model Organism Trichuris muris - Forman, Ruth; Partridge, Frederick A.; Sattelle, David B.; Else, Kathryn J. (Frontiers in Tropical Diseases, 2021)
Trichuris muris, is the murine parasite and widely deployed model for the human whipworm Trichuris trichiura, a parasite that infects around 500 million people globally. Trichuriasis is a classical disease of poverty with a cycle of re-infection due to the continual exposure of humans, particularly children, to infective eggs, which contaminate the soil in endemic areas. Indeed, modelling studies of trichuriasis have demonstrated that the low efficacy rate of current anthelmintics combined with the high possibility of re-infection from the reservoir of infective eggs within the environment, mean that the elimination of morbidity due to trichuriasis is unlikely to occur. Despite the importance of the infective egg stage in the perpetuation of infections, understanding the biology of the Trichuris ova has been neglected for decades. Here we perform experiments to assess the impact of temperature on the embryonation process of T. muris eggs and describe in detail the stages of larval development within these eggs. In keeping with the early works performed in the early 1900s, we show that the embryonation of T. muris is accelerated by an elevation in temperature, up to 37°C above which eggs do not fully develop and become degenerate. We extend these data to provide a detailed description of T. muris egg development with clear images depicting the various stages of development. To the best of our knowledge we have, for the first time, described the presence of birefringent granules within egg-stage larvae, as well as providing a qualitative and quantitative description of a motile larval stage prior to quiescence within the egg. These experiments are the first step towards a better understanding of the basic biology which underlies the process of egg embryonation. With the threat of elevation in global temperatures, the accelerated embryonation rate we observe at higher temperatures may have important consequences for parasite transmission rates and prospective modelling studies. In addition, a deeper understanding of the Trichuris ova may allow the development of novel control strategies targeting the egg stage of Trichuris in the environment as an adjunct to MDA.